Queen's Park Hotel, Trinidad, B.W.I. - (:unkn) unknown (Queen's Park Hotel Co. Ltd., Trinidad, 2010)
The Queen's Park Hotel, located in Port of Spain on the Southern side of the Queen's Park Savannah, was first opened in January 1895. There is a trolley car to the left. Postcard number 43.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Trees--Trinidad and Tobago; Palms--Trinidad and Tobago; Pedestrians--Trinidad and Tobago; [1900]; Hospitality industry--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Transportation--Trinidad and Tobago; Trolley cars--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Men--Trinidad and Tobago; Hats--Trinidad and Tobago; Fences--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)